Electromagnetic Fields for the Regulation of Neural Stem Cells. (28th August 2017) - Cui, Mengchu; Ge, Hongfei; Zhao, Hengli; Zou, Yongjie; Chen, Yujie; Feng, Hua
Abstract : Localized magnetic fields (MFs) could easily penetrate the scalp, skull, and meninges, thus inducing an electrical current in both the central and peripheral nervous systems, which is primarily used in transcranial magnetic stimulation (TMS) for inducing specific effects on different regions or cells that play roles in various brain activities. Studies of repetitive transcranial magnetic stimulation (rTMS) have led to novel attractive therapeutic approaches. Neural stem cells (NSCs) in adult human brain are able to self-renew and possess multidifferential ability to maintain homeostasis and repair damage after acute central nervous system. In the present review, we summarized the electrical activity of NSCs and the fundamental mechanism of electromagnetic fields and their effects on regulating NSC proliferation, differentiation, migration, and maturation. Although it was authorized for the rTMS use in resistant depression patients by US FDA, there are still unveiling mechanism and limitations for rTMS in clinical applications of acute central nervous system injury, especially on NSC regulation as a rehabilitation strategy. More in-depth studies should be performed to provide detailed parameters and mechanisms of rTMS in further studies, making it a powerful tool to treat people who are surviving with acute central nervous system injuries.